2020
DOI: 10.1088/1361-6528/ab96e1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of GaAs nanowire growth seeded by Ag and Au colloidal nanoparticles on silicon

Abstract: We present a comparative study of GaAs nanowire growth on Si(111) substrates by molecular beam epitaxy with the assistance of Au and Ag colloidal nanoparticles. Our approach allows the synthesis of nanowires with different catalyst materials in separate sectors of the same substrate within the same epitaxial process. We match the experimental results to the modeling of chemical potentials and nanowire length distributions to analyze the impact of silicon incorporation into the catalyst droplets on the growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Studies have shown that the material/composition, shape, position, and contact angle of the catalytic droplet strongly affect the NW properties, such as size, morphology, crystal structure, and doping. [153][154][155][156][157] Prior to wire growth, the metal catalysts are typically annealed at high temperature to deoxidize the surface and alloy the catalyst with the semiconductor material, promoting the growth of 〈111〉-oriented NWs. Instead, without annealing the Au catalyst at high temperature and using poly-L-lysine surface pretreatment, Krishnamachari et al successfully obtained vertical [001] InP NWs on InP (001) by MOCVD.…”
Section: Catalyst Engineeringmentioning
confidence: 99%
“…Studies have shown that the material/composition, shape, position, and contact angle of the catalytic droplet strongly affect the NW properties, such as size, morphology, crystal structure, and doping. [153][154][155][156][157] Prior to wire growth, the metal catalysts are typically annealed at high temperature to deoxidize the surface and alloy the catalyst with the semiconductor material, promoting the growth of 〈111〉-oriented NWs. Instead, without annealing the Au catalyst at high temperature and using poly-L-lysine surface pretreatment, Krishnamachari et al successfully obtained vertical [001] InP NWs on InP (001) by MOCVD.…”
Section: Catalyst Engineeringmentioning
confidence: 99%
“…Introduction of a foreign catalyst is a beneficial step for obtaining highquality InAs nanowires [38,[45][46][47]. However, InAs nanowires grown by this manner always have random growth directions [20,38,41,48] owing to the non-polar nature and the unavoidable oxidation of the Si substrates [49]. As far as we known, only the ultrathin nanowires (the diameter ∼10 nm) can be vertically grown on Si substrates [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Подобные наноструктуры имеют большой потенциал для ряда технологических применений, например, в детекторах газа [2][3][4], транзисторах [5] и датчиках давления [6]. Как правило, квазиодномерные SiC-наноструктуры, включая нанотрубки, синтезируют " снизу-вверх" в рамках механизма паржидкость-кристалл (ПЖК) с использованием различных катализаторов роста [7][8][9][10]. Также их формирование может осуществляться путем самокаталитического роста, с помощью масок [11] или по механизму пар-кристаллкристалл (ПКК) [12].…”
Section: Introductionunclassified